IMPROVING QUALITY THROUGH THE LEAN SIX SIGMA APPROACH - Hasanah, Rizkiyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article discusses improving quality through the lean six sigma approach at SMA Nurul Jadid Paiton. This research uses a qualitative case study approach, the research subjects consist of the Principal and several Deputy Heads. Data collection techniques use interviews, documentation, observation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The focus of this research is that the researcher wants to describe improving quality through the lean six sigma approach at SMA Nurul Jadid Paiton. The research results show that quality improvement through the lean six sigma approach at SMA Nurul Jadid Paiton greatly improve the quality of the institution through the five stages implemented , namely _ _ Define , Measure , Analyze , Improve And Control . We can see from the various performances that have been carried out by the staff in accordance with the Lean Six Sigma Approach or not, and we must be more careful in the performance or prioritization of human resources at Nurul Jadid High School . Improving the quality of educational institutions through the Lean Six Sigma Approach is very superior, this shows several positions between the good and bad approaches of the Lean Six Sigma Approach. And the Nurul Jadid High School institution proves that through the processes of the head and his subordinates they are the spearhead of improving the quality of the institution, and Nurul Jadid High School proves this with good performance, the results are also better through this Lean Six Sigma Approach. Nurul Jadid High School .